Assessment Practices at School Stage : The Case of the CCE – a School-based Assessment Implemented by the CBSE in its Affiliated Schools - Sivaraman, Dr Uma (THE PRIMARY TEACHER, 2012)
The aim of education is to prepare citizens for a meaningful, productive life. Evaluation should provide credible feedback on the extent to which this objective is achieved as well as for effecting further improvement in the teaching and learning processes. Current evaluation practices are highly inadequate and do not provide a complete picture of the individual’s abilities towards fulfilling the aim of education. In schools, the term evaluation is synonymous with examination which has long been the only measurement of student’s achievement. The word examination is associated with stress and anxiety for learners. Thus, the examinations negatively influence the testing and assessment carried out in the schools. On the other hand, if evaluation is integrated with the teaching-learning process, it will be meaningful and lead to diagnosis, remedial action and improvement in learning. There is a need to have a shift in instruction and assessment strategies so that desirable changes can be achieved. Assessment must seek to present a complete picture of the targeted learning. The areas spanning around knowledge, skills and behaviour must be appropriately covered within the curriculum determined as per the actual importance accorded to them in the curricula. Moreover, assessment must be based on clear standards, expressed in terms of learning to be achieved. The purpose of assessment must not only be to measure and judge; it must also help to improve learning as an ongoing process in education